ASSISTANCE TO THE NATURAL BATHING TOURISM MANAGEMENT COMMUNITY NAMU SIRA SIRA - Riza, Ade Ros; Valianto, Budi; Saputra, Hendra; Marpaung, Deni Rahman (Journal of Community Research and Service, 2024)
The aim of this community service activity is to implement one of the tridharmas of higher education, and help manage the Namu Sira-Sira natural bathing tourist attraction, Durian Lingga Village, Sei Bingei District, Langkat Regency. The main problem faced by partners is that in managing this tourist attraction, there is no financial management, no cleanliness management of the tourist location, no banner plan for the tourist location. The output in this activity is 1). Managers have the ability to create simple financial reports 2). Availability of good and appropriate hygiene management and hygiene advice. 3). Articles published in online ISSN journals. 4). There are social media accounts that managers use to market tourist attractions. This activity was carried out in Durian Lingga Village, Sei Bingei District, Langkat Regency.  This location is 55 km from Medan State University, a distance of 1 hour. This location was chosen because of the excellent tourism potential that can be developed for recreational sports, and can provide income for the surrounding community.